Respuesta :

Answer: -2

Step-by-step explanation:

The information in the question can be used to form an equation which goes thus:

2nd term = a + d = 4 ...... i

5th term = a + 4d = 22 ....... ii

From equation i

a = 4 - d ........ iii

Put equation iii into ii

a + 4d = 22

(4 - d) + 4d = 22

4 - d + 4d = 22

4 + 3d = 22

3d = 22 - 4

3d = 18

d = 18/3

d = 6

Commons difference is 6

Since a + d = 4

a + 6 = 4

a = 4 - 6

a = -2

The first term is -2

The first term of the fibonacci like sequence whose second term is 4 and whose fith term is 22 is -2

Given:

second term:

a + d = 4

fifth term:

a + 4d = 22

where

a = first be term

d = common difference

a + d = 4 (1)

a + d = 4 (1)a + 4d = 22 (2)

subtract (1) from (2)

4d - d = 22 - 4

3d = 18

d = 18 / 3

d = 6

substitute into (1)

a + d = 4 (1)

a + 6 = 4

a = 4 - 6

a = -2

Therefore, the first term of the sequence is -2

Read more:

https://brainly.com/question/15165519